Problems Faced by Elementary School Students in the Online Learning Process during the COVID-19 Pandemic - Safira Azzahra; Rina Maryanti; Verra Wulandary (Universitas Pendidikan Indonesia (UPI), 2022)
The COVID-19 pandemic requires the education system which was originally face-to-face in schools to be switched to distance learning or also known as online learning (in the network). The purpose of this research is to find out what are the problems faced by students during the online learning process. In this study, we used a descriptive method, with primary data. The results obtained indicate that there are problems faced in the distance learning process, limited learning tools, limited internet access and internet quota. It is hoped that after this research, the problems can be immediately addressed and become an evaluation for various parties to continue to improve the quality of distance learning to be more effective. It is hoped that after this research, the problems can be immediately addressed and become an evaluation for various parties to continue to improve the quality of distance learning to be more effective. It is hoped that after this research, the problems can be immediately addressed and become an evaluation for various parties to continue to improve the quality of distance learning to be more effective.